The survey of tinea capitis and scalp dermatophyte carriage in nursing home residents. (18th May 2017) - Lin, Chien-yio; Lo, Hsiu-Jung; Tu, Ming-Gene; Ju, Yu-Ming; Fan, Yun-Chen; Lin, Chih-Chao; Chiang, Ya-Ting; Yang, Yun-Liang; Chen, Kai-Ting; Sun, Pei-Lun
Abstract: Tinea capitis is a contagious dermatophyte infection of scalp and associated hairs. On the other hand, asymptomatic carriage is a status of positive dermatophyte scalp culture, but without signs or symptoms of tinea capitis, and no evidence of hair shaft invasion confirmed by direct microscopy. Tinea capitis and asymptomatic carriage mostly occur in children, but adult females are becoming another population in recent decades. In this study, we focused on the prevalence and related fungi of tinea capitis and asymptomatic carriage in elderly by the shampoo brush method, as well as the source of transmission, in 10 nursing home residents. Two hundred and thirteen residents were screened, and 186 isolates were identified, of which only three were dermatophytes (1.4%). The scalp dermatophyte isolates were identified as Trichophyton rubrum by morphological characters and sequences comparisons in all three cases. After revisiting, these cases were proved to be asymptomatic carriers by negative microscopic and culture examination; however, two cases were found to have concurrent tinea pedis and onychomycosis, which were identified as T. rubrum and Trichophyton interdigitale . The source of the T. rubrum scalp carriage may come from tinea elsewhere on the body of the same subject or from other people in the same institute. Finding and treating the source of carriage, as well as treating scalp carriage patients according to the colony counts, may help prevent disease spreading.